Genetic and phenotypic characterization of manufacturing seeds for a tetravalent dengue vaccine (DENVax). - Claire Y-H Huang; Richard M Kinney; Jill A Livengood; Bethany Bolling; John J Arguello; Betty E Luy; Shawn J Silengo; Karen L Boroughs; Janae L Stovall; Akundi P Kalanidhi; Aaron C Brault; Jorge E Osorio; et al. (Public Library of Science (PLoS), 2013)
We have developed a manufacturing strategy that can improve the safety and genetic stability of recombinant live-attenuated chimeric dengue vaccine (DENVax) viruses. These viruses, containing the pre-membrane (prM) and envelope (E) genes of dengue serotypes 1-4 in the replicative background of the attenuated dengue-2 PDK-53 vaccine virus candidate, were manufactured under cGMP.After deriving vaccine viruses from RNA-transfected Vero cells, six plaque-purified viruses for each serotype were produced. The plaque-purified strains were then analyzed to select one stock for generation of the master seed. Full genetic and phenotypic characterizations of the master virus seeds were conducted to ensure these viruses retained the previously identified attenuating determinants and phenotypes of the vaccine viruses. We also assessed vector competence of the vaccine viruses in sympatric (Thai) Aedes aegypti mosquito vectors.All four serotypes of master vaccine seeds retained the previously defined safety features, including all three major genetic loci of attenuation, small plaques, temperature sensitivity in mammalian cells, reduced replication in mosquito cell cultures, and reduced neurovirulence in new-born mice. In addition, the candidate vaccine viruses demonstrated greatly reduced infection and dissemination in Aedes aegypti mosquitoes, and are not likely to be transmissible by these mosquitoes. This manufacturing strategy has successfully been used to produce the candidate tetravalent vaccine, which is currently being tested in human clinical trials in the United States, Central and South America, and Asia.